2010
DOI: 10.1007/s10552-010-9503-z
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime exposure to arsenic in drinking water and bladder cancer: a population-based case–control study in Michigan, USA

Abstract: Objective Arsenic in drinking water has been linked with the risk of urinary bladder cancer, but the dose–response relationships for arsenic exposures below 100 µg/L remain equivocal. We conducted a population-based case–control study in southeastern Michigan, USA, where approximately 230,000 people were exposed to arsenic concentrations between 10 and 100 µg/L. Methods This study included 411 bladder cancer cases diagnosed between 2000 and 2004, and 566 controls recruited during the same period. Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 39 publications
(56 reference statements)
3
79
1
1
Order By: Relevance
“…apples, tomatoes, and cornelian cherries) between the 1920s and 1950s (Jomova et al, 2011;Letašiová et al, 2012). (Meliker et al, 2010;Steinmaus et al, 2003). Findings of a study in Bangladesh showed that mortality risks doubled after consumption of arsenic-contaminated water (Burger et al, 2013).…”
Section: -Nutritional Factorsmentioning
confidence: 99%
“…apples, tomatoes, and cornelian cherries) between the 1920s and 1950s (Jomova et al, 2011;Letašiová et al, 2012). (Meliker et al, 2010;Steinmaus et al, 2003). Findings of a study in Bangladesh showed that mortality risks doubled after consumption of arsenic-contaminated water (Burger et al, 2013).…”
Section: -Nutritional Factorsmentioning
confidence: 99%
“…Human diseases caused by As contamination include various cancers, liver disease, cardiovascular disease, and an increase in mortality from pulmonary tuberculosis [22][23][24][25][26][27][28]. Groundwater that contains As concentrations >10 μg/L limit set by the World Health Organization (WHO) places more than ten million people at risk from arsenicosis.…”
Section: Arsenic Chemistry Geochemistry Prevalence and Toxicitymentioning
confidence: 99%
“…Groundwater that contains As concentrations >10 μg/L limit set by the World Health Organization (WHO) places more than ten million people at risk from arsenicosis. Locales ranging from Southern Bangladesh, India, Argentina, Chile, and Vietnam have groundwater sources with As concentrations >10 μg/L [2,3,6,25,26,[28][29][30][31][32][33].…”
Section: Arsenic Chemistry Geochemistry Prevalence and Toxicitymentioning
confidence: 99%
“…An underlying assumption in these analyses is The research proved some preliminary data in an on-going case-control bladder cancer study. Recently, however, using standard statistical methods, the authors could not establish a relation between low-level arsenic exposure and bladder cancer [141] Lymphoma and leukaemia…”
Section: On the Use Of Social Deprivation Indicesmentioning
confidence: 99%